2020
DOI: 10.1021/acs.energyfuels.0c01374
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Heterogeneous Acid Catalyst DICAT-1 for One-Pot Conversion of Sucrose into 5-(Hydroxymethyl)furfural

Abstract: 5-(Hydroxymethyl)­furfural (HMF) is a trending biogenic platform molecule for the production of multiple energy, fuel, and chemical products, and it can be synthesized by using C6 sugars and/or its oligomers and polymers. In the present paper, the heterogeneous solid acid catalyst DICAT-1, with characteristic properties, exhibited one-pot conversion of sucrose into 5-HMF. The DICAT-1 triggered in-situ hydrolysis, isomerization, and dehydration of sucrose to yield 5-HMF in the presence of the low boiling point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…HMF could be effectively extracted into the organic layer, and the further degradation of HMF to levulinic acid and formic acid could be avoided. 59 Further increased the added water content to 40% and 60%, the yield of HMF decreased sharply at all temperatures except at 100 °C. Ulf Prüße has reported that the rehydration of HMF to levulinic acid and formic acid was favoured with increasing content of water in the low-boiling solvent HFIP.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…HMF could be effectively extracted into the organic layer, and the further degradation of HMF to levulinic acid and formic acid could be avoided. 59 Further increased the added water content to 40% and 60%, the yield of HMF decreased sharply at all temperatures except at 100 °C. Ulf Prüße has reported that the rehydration of HMF to levulinic acid and formic acid was favoured with increasing content of water in the low-boiling solvent HFIP.…”
Section: Resultsmentioning
confidence: 92%
“…HMF could be effectively extracted into the organic layer, and the further degradation of HMF to levulinic acid and formic acid could be avoided. 59 Further increased the added water content to 40% and 60%, the yield of HMF decreased sharply at all temperatures except at 100 C. Ulf Prüße has reported that the rehydration of HMF to levulinic acid and formic acid was favoured with increasing content of water in the low-boiling solvent HFIP. 60 Simultaneously, it was observed that the yield of HMF remained stable in a range of water content (0-20% water content) at 110 C and 120 C. Therefore, the appropriate water content was benecial for the hydrolysis of carbohydrate to HMF.…”
Section: Water Contentmentioning
confidence: 94%
“…31 The carbohydrate conversion and HMF yield were calculated according to the previous report. 32 The formic acid and levulinic acid were detected by HPLC with a UV detector (210 nm) using H 2 SO 4 as a mobile phase with a flow rate of 0.8 mL•min −1 at 40 °C. The formic acid and levulinic acid were calculated based on the previous report.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Currently, HMF production was achieved through the transformation of various carbohydrate sources including monosaccharides or polysaccharides (derived from the hydrolysis of biomass sources). Fructose, one of the monosaccharides being derived from biomass, is considered to be a preferred starting feedstock for HMF synthesis via a chemical catalytic route, since its furan structure is easier to be converted with high selectivity toward HMF than the pyran structure of glucose and other polysaccharides . Conversion of fructose to HMF has thus been conducted in wide ranges of reaction solvents, such as water, organic solvent, , and aqueous–organic biphasic solvent systems. , However, HMF in acid–aqueous solutions is extremely unstable, and it can be further degraded into undesired side products such as levulinic acid (LA) and formic acid through rehydration ,, and soluble and insoluble polymers known as humins through self- or cross-polymerization. , The selectivity toward HMF can be improved in organic solvents [e.g., dimethylsulfoxide (DMSO)] or water–organic solvent biphasic systems (e.g., H 2 O/MIBK) as the results of the suppressed side reactions. However, organic solvents with a high toxicity and boiling point are disfavored for industrial HMF production, considering the energy consumption of subsequent separation of HMF and the negative environmental impact of its toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…6−10 Fructose, one of the monosaccharides being derived from biomass, is considered to be a preferred starting feedstock for HMF synthesis via a chemical catalytic route, since its furan structure is easier to be converted with high selectivity toward HMF than the pyran structure of glucose and other polysaccharides. 11 Conversion of fructose to HMF has thus been conducted in wide ranges of reaction solvents, such as water, 12 organic solvent, 13,14 and aqueous−organic biphasic solvent systems. 15,16 However, HMF in acid−aqueous solutions is extremely unstable, and it can be further degraded into undesired side products such as levulinic acid (LA) and formic acid through rehydration 7,17,18 T h i s c o n t e n t i s and soluble and insoluble polymers known as humins through self-or cross-polymerization.…”
Section: Introductionmentioning
confidence: 99%